Transformasi Dan Tantangan Keuangan Dan Perbankan Syariah - Berliana Putri; Mohd Winario; Zubaidah Assyifa (EL-EMIR Institute, 2026)
The Islamic finance and banking industry has experienced significant development in recent decades, particularly in Indonesia, the country with the largest Muslim population in the world. This growth is characterized by an increasing number of Islamic financial institutions, product innovation, and increasingly strong regulatory support. This article examines the transformation of the Islamic finance sector in the digital era, the challenges of regulation, and the opportunities for developing products and services based on Islamic principles. Using a descriptive-analytical approach, this article discusses the basic concepts of Islamic banking, its historical evolution, the variety of Islamic financial products such as profit-sharing financing and buying and selling, and the dynamics of industry development amidst technological change. The study results indicate that although the Islamic banking industry faces various challenges, such as low Islamic financial literacy, limited human resources, and intense competition with conventional banking, its growth potential remains significant. This is supported by the use of financial technology (fintech), increased financial inclusion, and increasingly conducive government policies. Therefore, innovative and collaborative strategies are needed to strengthen the competitiveness of the Islamic finance industry in the future.